Graves' Ophthalmopathy on (68)Ga-DOTANOC Positron Emission Tomography/Computed Tomography - Arora, Saurabh (Indian J Nucl Med, 2019)
Graves' ophthalmopathy (GO) involves autoimmune activation of fibroblasts, resulting in chronic inflammatory reaction. Somatostatin receptors are expressed in the cells associated with chronic inflammation. We hereby present patients with active GO, with delayed response to the standard treatment regimen, in whom (68)Ga-DOTANOC positron emission tomography/computed tomography (PET/CT) was planned to evaluate the orbital inflammation. (68)Ga-DOTANOC PET/CT shows no physiological orbital muscle uptake. It can provide information which may possibly of utility in response assessment and also screening patients who fail to respond to conventional treatment, for newer therapies such as long-acting somatostatin analogs.